Transformative Learning: a Concept and Powerful Vision for Adult Education (Anwer Khan Modern Medical College Journal, 2017)
Transformative learning is a process of learning that individuals to changes their critically assumptions and beliefs and consciously making and implementing plans that bring about new ways. It is a fundamentally rational and analytical process. It is also a process of getting beyond gaining factual knowledge alone to instead become learns in some meaningful way. It involves questioning assumptions, beliefs and values, and considering multiple points of view, while always seeking to verify reasoning. This learning is to make interpretations from the person's own beliefs, judgments and feelings and consciously define the meaning of the experience1 or a process of learning that creates a substantial change in the habits, ideas and/or outlook of an individual. This article highlights concept and theories that deals with the paradigm shift of changes needed among adult learners, role of educators and learners towards development of individual and social lives in addition to existing perspective (traditional) of teaching & learning practice. Practices of transformative learning vision and process in adult education have the scope to bring improved critical thinking and a way of changing life style.Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 128-131